Management practices of MSMEs: A Case Study of Punjab - Pasricha , J.S.; Shiva, (Gyan Management Journal, 2013)
Worldwide small business is referred as engine of growth. In India small scale industry not only contributes significantly in GDP, employment and exports but also promises growth transcending various sectors, sections and regions. As a matter of fact, MSMEs are incubators of entrepreneurship often driven by individual creativity and innovation. However, if this sector has to survive and grow, amidst the current global scenario it is important that it delivers quality goods and services at competitive cost, this can be accomplished only if an enterprise follows proper management practices. Several research studies have shown relationship between firm's management practices and performance of the SMEs (Peou 2009, Blackman 2003), Baldwin et al., 1997) substantiated this view and found that in 71 % of the failed firms, deficiencies in both general and financial management are the major causes of failure. In his work/research, Mehra (1985) also found that lack of sound marketing practices were responsible for poor performance of small enterprises in Punjab. Sharma (1976) attributed the success of an enterprise on sound management practices and financial discipline. According to him, since small enterprises are managed by the owner himself or his family members who may or may not be well versed with modern management. The success of an enterprise is lar gely determined by satisfactory management of inventory, budgeting, sound financial, marketing and human resource management. These areas should be deeply studied by owner manager and information collected should be utilized to plan and control the activities of a unit. The management of inventory and finance is very important of all. Many small enterprises fall sick because of improper handling of these areas of management. With innovations, an entrepreneur can create new avenues and opportunities for its growth.
Keywords: Worldwide; GDP; goods and services; management; innovations